2022
DOI: 10.3389/fpubh.2022.847282
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of COVID-19 Vaccine Acceptance and Reluctance Among Staff Working in Public Healthcare Settings of Saudi Arabia: A Multicenter Study

Abstract: ObjectiveThe study aimed to evaluate the novel coronavirus disease 2019 (COVID-19) vaccination acceptance and reluctance among staff working in Saudi healthcare facilities.MethodsA cross-sectional study was conducted during April – May 2021, among healthcare workers in five public hospitals under the National Guards Health Association located in Alahsa, Dammam, Jeddah, Madinah, and Riyadh. The study used a questionnaire in English language, which was distributed through official email communication among healt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 25 publications
1
10
0
Order By: Relevance
“…The present study showed that about 70% of the participants reported a moderate to high acceptance of the COVID-19 vaccine. Several other Saudi studies were almost in line with our results, which showed that 62-71% of Saudi citizens and Saudi residents have a good acceptance of COVID-19 vaccines (Narapureddy et al 2021;Alqahtani 2021;Alshahrani et al 2021;Maqsood et al 2022;Al-Mohaithef and Padhi 2020;Fadhel 2021;Yahia et al 2021;Elharake et al 2021). However, Khalafalla et al reported that 83.6% of Jazan University students were willing to take the COVID-19 vaccine, which was described as having a high acceptance rate compared to most studies conducted in Saudi Arabia (Khalafalla et al 2022).…”
Section: Discussionsupporting
confidence: 92%
“…The present study showed that about 70% of the participants reported a moderate to high acceptance of the COVID-19 vaccine. Several other Saudi studies were almost in line with our results, which showed that 62-71% of Saudi citizens and Saudi residents have a good acceptance of COVID-19 vaccines (Narapureddy et al 2021;Alqahtani 2021;Alshahrani et al 2021;Maqsood et al 2022;Al-Mohaithef and Padhi 2020;Fadhel 2021;Yahia et al 2021;Elharake et al 2021). However, Khalafalla et al reported that 83.6% of Jazan University students were willing to take the COVID-19 vaccine, which was described as having a high acceptance rate compared to most studies conducted in Saudi Arabia (Khalafalla et al 2022).…”
Section: Discussionsupporting
confidence: 92%
“…This could be due to the difference in the availability and promotion of COVID educational information or cultural factors. Further, the study's COVID‐19 vaccine acceptance was low compared to other recent studies 33–37 . A difference in the study period could be the reason for the discrepancy.…”
Section: Discussionmentioning
confidence: 62%
“…Further, the study's COVID-19 vaccine acceptance was low compared to other recent studies. [33][34][35][36][37] A difference in the study period could be the reason for the discrepancy. Also, misinterpretations of information from the prior COVID-19 pandemic, healthcare workers may be discouraged from taking the COVID-19 vaccination.…”
Section: Determinants Of the Novel Coronavirus Vaccine Acceptancementioning
confidence: 99%
“…Certain sociodemographic factors were linked to vaccine acceptance, including being male (n = 7) [ 26 , 27 , 29 , 30 , 32 , 34 , 62 ], being older (n = 2) [ 30 , 62 ], and being married (n = 2) [ 24 , 26 ]. Other predictors of vaccine acceptance included a high-risk perception of getting COVID-19 (n = 4) [ 25 , 26 , 30 , 34 ], belief in the COVID-19 vaccine’s benefit (n = 3) [ 25 , 26 , 29 ], positive attitudes towards influenza vaccine (n = 3) [ 26 , 30 , 62 ], belief that the vaccine should be mandatory (n = 3) [ 24 , 25 , 30 ], vaccine convenience/lack of barriers towards receiving the vaccines, (n = 2) [ 24 , 25 ], working directly in high-risk settings (n = 2) [ 26 , 30 ], and history of chronic illness (n = 1) [ 32 ].…”
Section: Resultsmentioning
confidence: 99%
“…Most of the studies were from Saudi Arabia (n = 15) [19][20][21][23][24][25][26][27][28][29][30][31][32][33][34] followed by Egypt (n = 6) [35][36][37][38][39][40], Jordan (n = 3) [22,41,42], Palestine (n = 3) [43][44][45], United Arab Emirates (n = 3) [46][47][48], Iraq (n = 2) [49,50], Lebanon (n = 2) [51,52], and Oman (n = 2) [53,54]. Only one study was found for each of the following countries: Kuwait [55], Libya [56], Morocco [57], Qatar [58], Sudan [59], and Tunisia [60].…”
Section: Characteristics Of the Included Studiesmentioning
confidence: 99%